A Kinetic and Factorial Approach to Study the Effects of Temperature and Salinity on Growth and Toxin Production by the Dinoflagellate Alexandrium ostenfeldii from the Baltic Sea - Salgado, Pablo; Vázquez, José A.; Riobó, Pilar; Franco, José M.; Figueroa, Rosa I.; Kremp, Anke; Bravo, Isabel (PLOS ONE, 2015)
Alexandrium ostenfeldii is present in a wide variety of environments in coastal areas worldwide and is the only dinoflagellate known species that produces paralytic shellfish poisoning (PSP) toxins and two types of cyclic imines, spirolides (SPXs) and gymnodimines (GYMs). The increasing frequency of A. ostenfeldii blooms in the Baltic Sea has been attributed to the warming water in this region. To learn more about the optimal environmental conditions favoring the proliferation of A. ostenfeldii and its complex toxicity, the effects of temperature and salinity on the kinetics of both the growth and the net toxin production of this species were examined using a factorial design and a response-surface analysis (RSA). The results showed that the growth of Baltic A. ostenfeldii occurs over a wide range of temperatures and salinities (12.5–25.5°C and 5–21, respectively), with optimal growth conditions achieved at a temperature of 25.5°C and a salinity of 11.2. Together with the finding that a salinity > 21 was the only growth-limiting factor detected for this strain, this study provides important insights into the autecology and population distribution of this species in the Baltic Sea. The presence of PSP toxins, including gonyautoxin (GTX)-3, GTX-2, and saxitoxin (STX), and GYMs (GYM-A and GYM-B/-C analogues) was detected under all temperature and salinity conditions tested and in the majority of the cases was concomitant with both the exponential growth and stationary phases of the dinoflagellate’s growth cycle. Toxin concentrations were maximal at temperatures and salinities of 20.9°C and 17 for the GYM-A analogue and > 19°C and 15 for PSP toxins, respectively. The ecological implications of the optimal conditions for growth and toxin production of A. ostenfeldii in the Baltic Sea are discussed.